Efficacy of Anakinra on Multiple Coronary Arteries Aneurysms in an Infant with Recurrent Kawasaki Disease, Complicated by Macrophage Activation Syndrome - Grazia Bossi; Alessia Claudia Codazzi; Federica Vinci; Edoardo Clerici; Corrado Regalbuto; Carmela Crapanzano; Daniele Veraldi; Alice Moiraghi; Gian Luigi Marseglia (MDPI AG, 2022)
Kawasaki disease (KD) is rare in infants less than 3 months of age, and its recurrence is exceptional. Infants with KD are at higher risk of severe clinical presentation, therapy failure, complications and coronary aneurysms (CAAs), and this is the reason they deserve more aggressive therapy and a strict clinical follow-up. We report a 2-month-old male with KD, complicated by Macrophage Activation Syndrome (MAS). Despite timely and aggressive therapy with immunoglobulins, steroids and aspirin, multiple CAAs developed. Two-month therapy with anakinra completely reverted all the aneurysms. After six months, the infant experienced KD relapse and was successfully re-treated with immunoglobulins, steroids and aspirin. A strict echocardiographic follow-up did not show recurrence of aneurysms. Two years later, the child is healthy, without cardiac sequelae. In our experience, anakinra was effective in reverting multiple aneurysms and its effect proved to be long-lasting, even in front of KD recurrence. Based on this evidence, it seems reasonable to hypothesize not to limit the use of anakinra as rescue therapy for complicated or refractory KD, but to consider the possibility of adding it to first-line therapies for some subgroups of very-high-risk patients, in order to strengthen the prevention of CAAs.